A case to de-register and prohibit the use of Paraquat in Nigeria - Udensi, U.E.; Ekpere, J.; Irtwange, S.; Kolo, M.G.M.; Yahaya, M.K.; Ladele, A.; Sanni, L.; Yusuf, G.; Ekeleme, F.; Atser, G.; Ibe, E.; Dixon, A. (International Institute of Tropical Agriculture, 2020)
Paraquat is regarded as one of the most highly toxic herbicides in the world to have been marketed in the last 60 years. Its use is reported in more than 100 countries and on more than 100 crops in different cropping systems. A desk study and rural appraisal undertaken in six States of Nigeria to assess the current status of use, perceptions of farmers and other stakeholders, and levels of toxicity confirmed high levels of risk to farmers’ health and the environment. The study indicated more than 20 brand or trade names for Paraquat with several variations in terms of the percentage of active ingredient. The brands most commonly used by farmers across the States are Dragon, Paraforce, Weed-off, Slasher, Paraquin, and Reliquat.